2021
DOI: 10.2166/wh.2021.268
|View full text |Cite
|
Sign up to set email alerts
|

Economic valuation meta-analysis of freshwater improvement in developed and developing countries. Are they different?

Abstract: The quality of drinking water differs across countries, so households show different levels of willingness to pay (WTP) to improve it, which is also influenced by their income levels. This study presents a meta-analysis using studies from 30 developed and developing countries, representing 4.7 billion inhabitants. At the international level, by standardizing these values (PPP) to international US dollars of 2011, developing countries show, on average, a greater WTP than developed countries relative to their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Empirical research has shown that there are a variety of factors that affect WTP, such as age, education, gender, marital status, occupation, household income, and the number of household members [21,22]. Other factors such as awareness of environmental protection, the relative importance of the environment to the economy, the ages of children in the household, the level of transparency of information and participation in the decision-making process, and the need for water quality improvements can also influence WTP [15,23,24]. For instance, Guilfoos et al [25] discovered that there were discrepancies between people's perceptions of water quality and the actual number of bacteria present in the water samples collected from households.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research has shown that there are a variety of factors that affect WTP, such as age, education, gender, marital status, occupation, household income, and the number of household members [21,22]. Other factors such as awareness of environmental protection, the relative importance of the environment to the economy, the ages of children in the household, the level of transparency of information and participation in the decision-making process, and the need for water quality improvements can also influence WTP [15,23,24]. For instance, Guilfoos et al [25] discovered that there were discrepancies between people's perceptions of water quality and the actual number of bacteria present in the water samples collected from households.…”
Section: Introductionmentioning
confidence: 99%